Phytochemical and Pharmacological Investigation on Onosma bracteatum Wall. - Rajapara, Aruna M; Bhatt, Vijay P; Shah, Mamta B (Asian Journal of Biological and Life Sciences)
Introduction: Onosma bracteatum is one of the important species of genus Onosma growing in Himalayas in India that has been used traditionally as a beneficial remedy for many diseases yet in unexplored scientifically. Objectives: The aim of study is to isolate and quantify compound and evaluation of antioxidant and cytotoxic potential of extract and fractions of whole plant of O. bracteatum. Materials and Methods: Total methanolic extract (TME) was prepared by Sohxlet extraction method and Successive solvent extraction of plant material was performed using Soxhlet apparatus to yield petroleum ether (A1), chloroform (A2), ethyl acetate (A3), n-butanol (A4) and water (A5) extracts. TME was subjected to qualitative phytochemical screening and determination of total phenolic content (TPC) and total flavonoid content (TFC). A1 was subjected for column chromatography and isolated compound was characterized by spectral analysis and quantified using HPTLC. Total antioxidant capacity (TAC), free radical scavenging activity (DPPH), nitric oxide scavenging assay and cytotoxicity through Brine Shrimp Lethality Assay (BSLA) of TME and fractions of O. bracteatum were conducted. Result and Discussion: Results of the study showed the presence of quinones, alkaloids, flavonoids, phenolics, coumarins, fixed oil and fat, carbohydrates and terpenoids in the TME of O. bracteatum. The TPC and TFC of O. bracteatum were found 14.5±0.00047 mg GAE/g of dry powder and 11.2±0.0014 mg RUE/g of dry powder respectively. Probable structure of isolated compound was 1,7-dihydroxy-3-methyl-9H-xanthene- 9-one and the amount of compound was found to be 0.17 ± 0.11 %w/w in the plant. Total antioxidant capacity was found higher in A4 (58.56±0.0015 μg BHTE/mg of dry extract). TME showed lowest EC50 value for the DPPH radical scavenging activity TME showed significantly higher activity compared to the A1, A2, A3, A4 and A5. The fraction A4 showed significantly higher nitric oxide scavenging activity compared to the TME, A1, A2, A3 and A5. For cytotoxicity test, A4 (IC50 =74.13μg/ml), A1 (IC50 =75.85μg/ml), A2 (IC50 =79.43μg/ml) showed equivalent cytotoxicity compared to TME, A3 and A5. The results indicate that the A4 may contain higher phenolics and flavonoids, on other hand A1 and A2 are rich in alkannin/shikonin and xanthon type of compounds in O. bracteatum. Conclusion: O. bracteatum possessed significant antioxidant and cytotoxic potential
Keywords: BSLA; DPPH; HPTLC; Onosma bracteatum; Phytochemicals